EFEK EKSTRAK DAGING BUAH PALA (Myristica fragrans Houtt.) TERHADAP HISTOPATOLOGI PANKREAS TIKUS PUTIH (Rattus norvegicus) DIABETES - Handayani, Sri Windi; S. Somadayo, Nur Asma; Fiskia, Ermalyanti; Nur, Amran (As-Syifaa Jurnal Farmasi, 2024)
Diabetes mellitus is a severe and persistent illness caused by insufficient production of insulin, a hormone responsible for regulating blood glucose levels, by the pancreas. Diabetes mellitus is a significant public health issue, and its incidence is expected to rise over the next several decades. This study aims to investigate the impact of nutmeg (Myristica fragrans Houtt) pulp extract on the pancreatic histopathology of diabetic white rats (Rattus novergicus). According to research findings, a dose of 100 mg/kgBW of nutmeg pulp extract has been found to effectively lower blood sugar levels without causing harm to the pancreas. On the other hand, doses of 200 mg/kgBW and 300 mg/kgBW of nutmeg pulp extract can drop blood sugar levels, but they have certain side effects. cause harm to the pancreas organ